If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60 + -6x = 12x + 15 Reorder the terms: 60 + -6x = 15 + 12x Solving 60 + -6x = 15 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 60 + -6x + -12x = 15 + 12x + -12x Combine like terms: -6x + -12x = -18x 60 + -18x = 15 + 12x + -12x Combine like terms: 12x + -12x = 0 60 + -18x = 15 + 0 60 + -18x = 15 Add '-60' to each side of the equation. 60 + -60 + -18x = 15 + -60 Combine like terms: 60 + -60 = 0 0 + -18x = 15 + -60 -18x = 15 + -60 Combine like terms: 15 + -60 = -45 -18x = -45 Divide each side by '-18'. x = 2.5 Simplifying x = 2.5
| 0.5x-1.36=12.34 | | 15=7x | | 26=8+u | | -3f=18-f | | -6x^2-x-4=0 | | 53-7x=15+12x | | 0=x^2+2y^2+4y-2x+1 | | d-23d= | | 28=5x+3(2x+11) | | (2xh)+(2xh)+(h+h)=180 | | 16x+9=15x-4 | | (X+7)(3x+5)=0 | | 3(4x-3.2)=5x-9.6 | | 3(2-3x)=52 | | 2x-4+3x=7x-3 | | 70x+90=90 | | 7x-5=5x-6 | | x^2-6x=22 | | 6u-9+3(2u+3)=4(u+3) | | 4(x+1.78)=3x | | 8n+16=8 | | 200x-0.08=600x+0.52 | | 3x+7=-2x+27 | | 6-6x=6x-10x+10 | | 3.9x-73=2.4x+5 | | 8z-24=6+2z | | 5m-7=10+3m | | 6.2=8x+1.4 | | 6-6x=6x-10+10 | | 6n-2=1 | | -4(v-4)=-7+37 | | 2y-8+14=-6 |